Systemic Risk and Stock Returns in During the Corona Pandemic: An Analytical Study of a Sample of Industrial Companies Listed in Iraq Security Exchange - نوري كاكه حمه العطار, خانم (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The issue of systemic risk and stock returns is one of the important topics that all companies seek, especially industrial companies, which aim to maximize their profits and reduce their risks. Now, the spread of the Corona pandemic has added a greater burden on companies as a result of the sudden changes they face, and their negative impact on companies performance. This led to a noticeable decline in the returns of its stocks and an increase in its risks, Itcan be seen that companies try to maintain their returns and avoid risks, and try to take measures to avoid those risks for fear of reaching bankruptcies and descending towards financial failure. Therefore, the relationship between stock returns and systemic risk is of great importance during the spread of the Corona pandemic. The research aims to test the strength of the relationship and the impact of the Corona pandemic on both stock returns and systemic risks. To achieve this goal, the research relied on the (Analytical and Econometrics) approach by using monthly data for a period (January 2019 - August 2021). Based on the data issued by the Iraq Stock Market for a sample of (7) industrial companies. A dummy variable of the Corona pandemic was used because of its great impact on industrial companies, and the research concluded that although, the Corona pandemic negatively affected all companies, the research sample, but the two companies manufacturing and marketing dates, the Iraqi carpet and furnishings company, are more affected by the pandemic compared to other companies, this is due to the change in demand for these commodities and the nature of their products, which led to the instability of their profits and the inability of the two companies to controlling the degree of risk due to the lack of modern methods for predicting unexpected changes. Finally, the research presented several recommendations, including that industrial companies should not stop its investments during the pandemic and try increase its sales, as a result of the management’s effectiveness in developing good plans, policies and programs that contribute to building an appropriate strategy and following it to keep potential changes of the internal and external environment and using them to modern tools and methods in preparation for facing future crises.